Cyber Criminal Policy In The Perspective Of Decency - Edy Sukendy; Bayu Bayu; Habib Munawar (International Asia Of Law and Money Laundering (IAML), 2022)
Cyber crime is one of the forms or a new dimension of evil today gets wide attention in the international world. One of the problems that is very unsettling and got the attention of various circles is the issue of cyber crime in the field decency which later became known by the term cyber adultery. That cyber adultery in essentially no different with crime/violation of decency in general, such as adultery. Cyber adultery/cyber sex can be viewed as satisfaction/excitement maya (virtual gratification) that is associated with sexual expression, and a new form of intimacy (a new type of intimacy). An intimate relationship or intimacy (intimacy) it can also contains the meaning of sexual intercourse or adultery. This means that cyber sex is a form of new from adultery. To overcome this problem, it takes its criminal policies in an effort crime prevention, which in essence is an integral part of the effort the protection of society (social defence) and the efforts of the social welfare (social welfare).